Odpowiedzi

Najlepsza Odpowiedź!
2009-09-19T23:19:08+02:00
X⁴+y⁴+z⁴ jeżeli x+y+z=0 i x²+y²+z²=a

x²+y²+z²=a /(²)
x⁴+y⁴+z⁴+2(x²y²+x²z²+y²z²)=a²

x+y+z=0 /(²)
x²+y²+z²+2(xy+xz+yz)=0==> a+2(xy+xz+yz)=0
xy+zx+yz=-a/2 /(²)
x²y²+x²z²+y²z²+2xyz(x²zy+xz²y+xzy²)=a²/4
x²y²+x²z²+y²z²+2xzy(x+y+z)=a²/4 ALE (x+y+z)=0 stąd
x²y²+x²z²+y²z²+2xzy•0=a²/4
x²y²+x²z²+y²z²=a²/4

powracam

x⁴+y⁴+z⁴+2(x²y²+x²z²+y²z²)=a² , podstawiam
x⁴+y⁴+z⁴+2•a²/4=a²
x⁴+y⁴+z⁴=a²/2

2009-09-20T01:28:13+02:00
X+y+z=0 /(²)
x²+y²+z²+2(xy+xz+yz)=0
a+2(xy+xz+yz)=0
xy+zx+yz=-a/2 |(²)
x²y²+x²z²+y²z²+2xyz(x²zy+xz²y+xzy²)=a²/4
x²y²+x²z²+y²z²+2xzy(x+y+z)=a²/4
ponieważ (x+y+z)=0, więc
x²y²+x²z²+y²z²=a²/4

od początku:
x²+y²+z²+2(xy+xz+yz)=0 |(²)
x⁴+y⁴+z⁴+2(x²y²+x²z²+y²z²)=a², podstawiamy "x²y²+x²z²+y²z²=a²/4"
x⁴+y⁴+z⁴+2•a²/4=a²
x⁴+y⁴+z⁴=a²/2